The Role Of Artificial Intelligence (AI) In Developing English Language Learner's Communication Skills - Rusmiyanto Rusmiyanto; Nining Huriati; Nining Fitriani; Novita Kusumaning Tyas; Agus Rofi’i; Mike Nurmalia Sari (Departement of Mathematics Education, 2023)
In today's globalized world, the increasing need for English language ability has highlighted the necessity of good language acquisition and communication abilities. Artificial Intelligence (AI) has emerged as a viable aid in the field of education, including language acquisition, as technology advances. This study does a literature review to investigate the function of AI in the development of communication skills in English language learners. The goal of this research is to look at the existing research and literature on the use of AI-based technologies in English language learning environments. The essay opens with an overview of artificial intelligence and its possible uses in education. It then looks into the various methods in which AI might help English language learners strengthen their communication skills, including speaking, listening, reading, and writing. The findings of this literature review suggest that AI has the potential to significantly enhance English language learners' communication skills by providing personalized and interactive learning experiences. However, further research is needed to explore the long-term effects and optimal integration of AI in language learning environments. In conclusion, this article highlights the transformative role of AI in English language education and its potential to address the diverse needs of language learners. By understanding the current state of research and exploring the opportunities and challenges presented by AI in language learning, educators and policymakers can make informed decisions to harness the benefits of AI technology and maximize its impact on developing effective communication skills among English language learners.